Analysis the Impact of Differentiated Instruction on Critical Diversity Literacy in Inclusive Education - Qorib, Muhammad (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2024)
The goal of this study is to examine the influence of critical diversity literacy on differentiation learning for students at Muhammadiyah University of North Sumatra, a sample of 30 students in two classes for one semester using different teaching approaches. The mix-method research method combines quantitative and qualitative mixed methodologies as well as explanatory sequential design strategies. Inferential t-test statistics, SEM, NVIVO, or WORDCLOUD are among the techniques employed. The results revealed that the diversified instruction learning model had a beneficial influence on learning critical reading of diversity literacy in inclusive education. The differentiated instruction learning model allows students to gain an in-depth understanding of their own diversity, learn to see and hone thinking and communication skills, increase self-confidence, and use critical thinking in viewing diversity in order to have a moderate attitude toward religion. Most students, it is considered, perceive Differentiated Instruction as an effective method of facilitating communication and comprehension in inclusive education courses.